Beliefs About Etiology and Treatment of Mental Illness Among Korean Presbyterian Pastors - Yamada, Ann-Marie (Journal of religion and health, 2019)
This descriptive study explored pastors' beliefs about etiology and treatment of mental illness. Surveys were completed by mail by 202 Korean and Euro-American Presbyterian clergy. Nearly one-third of Korean pastors viewed bad parenting and demon possession as very important causes of mental illness, in contrast to the more than two-thirds of Euro-American pastors who viewed genetics and chemical imbalances as the most important causes. Compared with their Euro-American counterparts, Korean pastors soundly endorsed spiritual treatment of mental illness. The findings of this study suggest the value of understanding the views of pastors working with populations that underutilize formal mental health services.